THE EFFECT OF USING IMPROMTPU SPEAKING TECHNIQUE ON STUDENTS’ ENGLISH-SPEAKING ABILITY - Khofifatulamni Khofifatulamni; Eliwarti Eliwarti; Muhammad Syarfi (Smart Education, 2025)
Abstract: This study aims to determine whether impromptu speaking affects students' English-speaking ability in the 2024–2025 school year at MAN 2 Kuantan Singingi. This quasi-experimental study employed a quantitative methodology and a pre-experiment, one group pretest, and post-test research design. Oral dialogue in a single scenario was the instrument used to gather the data, and SPSS 27 was used for analysis. The study's sample consisted of 40 11th generation students, while the population consists of all Pare Arabic and English Course students at MAN 2 Kuantan Singingi. According to the results, the experimental class's average pretest and posttest scores increased by 21 points. In contrast, the average student's score only rose 18 points above the pretest score in the controlled class, which employed traditional methods. Furthermore, the independent sample t-test result was 0.009, which is less than the alpha value of 0.05. The study's findings suggest that students' English-speaking skills improved as a result of impromptu speaking. Keyword: Impromptu speaking, English-speaking, English teaching Abstrak: Tujuan dari penelitian ini adalah untuk memastikan apakah berbicara dadakan Penelitian ini bertujuan untuk mengetahui apakah berbicara spontan memengaruhi kemampuan berbicara bahasa Inggris siswa pada tahun ajaran 2024–2025 di MAN 2 Kuantan Singingi. Penelitian kuasi-eksperimental ini menggunakan metodologi kuantitatif dan desain penelitian pra-eksperimen, satu kelompok, pra-tes, dan pasca-tes. Dialog lisan dalam satu skenario adalah instrumen yang digunakan untuk mengumpulkan data, dan SPSS 27 digunakan untuk analisis. Sampel penelitian terdiri dari 40 siswa generasi ke-11, sedangkan populasi terdiri dari semua siswa Kursus Bahasa Arab dan Bahasa Inggris Pare di MAN 2 Kuantan Singingi. Menurut hasil, skor pretest dan posttest rata-rata kelas eksperimen meningkat sebesar 21 poin. Sebaliknya, skor rata-rata siswa hanya naik 18 poin di atas skor pretest di kelas kontrol, yang menggunakan metode tradisional. Lebih jauh, hasil uji t sampel independen adalah 0,009, yang lebih kecil dari nilai alfa 0,05. Temuan penelitian menunjukkan bahwa keterampilan berbicara bahasa Inggris siswa meningkat sebagai hasil dari berbicara spontan. Kata kunci: Berbicara spontan, berbicara bahasa Inggris, pengajaran bahasa Inggris